Plesdasep Innovation: Fever-Reducing Plaster Using the Leaves of Dadap Serep (Erythrina subumbrans) as a First Aid Medium for Fever - Novitasari, Arum; Kurniawati, Anik; Septiana, Melisa (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah (Bapperida) Kabupaten Boyolali, 2023)
This research aims to: 1) Make an innovation of febrifuge plaster made from dadap serep leaves (Erythrina subumbrans), 2) Examine the effectiveness of the product in reducing fever, 3) Know people's preferences for the product. The method used in this study is an experimental method with a complete randomized design. The test was carried out by conducting a feasibility test of dadap serep leaves for plaster material and testing the effectiveness of plaster in reducing body temperature. The effectiveness test was conducted by applying warm water compresses to the first experimental group who had fever, plesdasep in the second experimental group, and comparing it with the control group that was not given plaster. After that, respondents were given a questionnaire to find out their preferences for Plesdasep. The results of this study are expected to provide an inexpensive alternative to fever treatment with ingredients that are easily available in nature. Dadap serep leaves were chosen as ingredients because they contain alkaloid compounds, flavonoids, and saponins that can reduce body temperature and are easily found in the surrounding environment. With this innovation, it is expected to provide an alternative treatment that is safe, cheap, and easily accessible for people who need first aid during fever.